Rate of Progression in Activity and Participation Outcomes in Exercisers with Parkinson’s Disease: A Five-Year Prospective Longitudinal Study - Stephanie A. Miller; Mindy Mayol; Elizabeth S. Moore; Audra Heron; Victoria Nicholos; Brian Ragano (Parkinson's Disease)
Background. Rates of progression of motor symptoms and physical performance show declines between 2% and 7% annually in community samples with Parkinson’s disease (PD). However, the effects of ongoing exercise behaviors on progression rates have not been considered. Objective. The primary purpose of this prospective, longitudinal study was to examine the annual rates of progression in activity and participation measures over five years in community-based exercisers with PD. Methods. A cohort of 55 regular exercisers with idiopathic PD was assessed at baseline and 1, 2, and 5 years. Regular exercise was defined as scores of 4-5 on the Stages for Readiness to Exercise Scale and a self-reported average of at least 60 minutes of exercise/week within six months of each testing session. Unadjusted and adjusted annual progression rates for activity and participation measures were calculated with a standardized equation of change from baseline. A linear mixed model with covariates of age at PD diagnosis and PD subtype was used to determine adjusted change scores. Results. Annual progression rates for unadjusted and adjusted variables were similar, and none exceeded 1.7% across time points for this group of exercisers with PD. Older age at PD diagnosis significantly contributed to faster progression of walking and balance functions. A nonlinear trajectory of the PD progression was demonstrated across most activity and participation outcomes. Conclusions. Annual progression rates demonstrated by this sample of exercisers were lower than those previously reported for motor decline in general samples with PD. Assessing activity and participation outcomes longitudinally at interim time points was important for understanding the trajectory of change over time. The lower rates of progression in this study warrant further investigation into the long-term effects of exercise in PD.